1994
DOI: 10.1002/zoo.1430130207
|View full text |Cite
|
Sign up to set email alerts
|

Changes in incubation sharing in one pair of captive California condors (Gymnogyps californianus)

Abstract: Three years of behavioral data were collected on incubation behavior in one pair of captive condors (Gymnogyps californiunus) at the San Diego Wild Animal Park. Data were collected from daily video tape reviews of the nest box. The amount of time each bird was in the nest box, and whether it was on or off the egg were recorded, along with any aggressive interactions observed in the nest. For the first 2 years, the female incubated the egg(s) significantly more than the male. During the third year, the male inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Consistent with the results of Spoon et al [], we found that pairs of cockatiels that successfully hatched offspring exhibited lower levels of intrapair aggression prior to breeding and were better able to coordinate incubation behavior during breeding trials. Our results support the notion that pair behavioral compatibility is associated with improved reproductive success in captivity [Baltz, ; Harvey et al, ; Spoon et al, ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the results of Spoon et al [], we found that pairs of cockatiels that successfully hatched offspring exhibited lower levels of intrapair aggression prior to breeding and were better able to coordinate incubation behavior during breeding trials. Our results support the notion that pair behavioral compatibility is associated with improved reproductive success in captivity [Baltz, ; Harvey et al, ; Spoon et al, ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, those pairs that exhibited a combination of low aggression and high nest activity were more likely to produce surviving offspring [Baltz, ]. Similar effects have also been seen in force‐paired California condors in captivity ( Gymnogyps californianus ), in which pairs classified as incompatible based on behavioral observations were less able to coordinate parental care [Harvey et al, ]. Additionally pairs of cockatiels ( Nymphicus hollandicus ; a small, socially‐monogamous Australian parrot) that exhibited higher levels of behavioral compatibility prior to breeding were also better able to synchronize incubation behavior and hatched a greater proportion of fertile eggs than less compatible pairs when breeding in captivity [Spoon et al, ].…”
Section: Introductionmentioning
confidence: 94%
“…com., our study) Andean Condors also indicate that males incubate, and may even forcibly displace females to incubate. Such behavior might be typical of New World vultures because male California Condors, Black Vultures, and Turkey Vultures also have important roles in incubating eggs and provisioning young (Coles 1944, Verner 1978, del Hoyo et al 1994, Harvey et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…At this time, all remaining wild condors were brought into captivity for an extensive captive-breeding program [Stoms et al, 1993;Snyder and Snyder, 2000;Alagona, 2004]. Breeding facilities used a strategy called ''double clutching'' to produce as many California condors in captivity as possible [Snyder and Hamber, 1985;Harvey et al, 2003Harvey et al, , 2004Nielsen, 2006;]. Double clutching involved pulling the first egg of the season to induce the breeding pair to lay another egg.…”
Section: Introductionmentioning
confidence: 99%